Clinical characteristics of neuropathic pain in leprosy and associated somatosensory profiles: a deep phenotyping study in India. (November 2019) - Haroun, Omer M.O.; Vollert, Jan; Lockwood, Diana N.; Bennett, David L.H.; Pai, Vivek V.; Shetty, Vanaja; Wakade, Anju V.; Khodke, Ashish S.; Schilder, Andreas; Pfau, Doreen; Enax-Krumova, Elena K.; Maier, Christoph; et al.
Abstract : Abstract: This study investigated the clinical characteristics and somatosensory profiles of patients suffering from leprosy in Mumbai, India. A cross-sectional deep profiling study was conducted in 86 patients with leprosy (with and without pain) using an extensive battery of phenotyping measures including structured clinical examination, psychological state (General Health Questionnaire [GHQ-12]), and a quality-of-life condition-specific instrument (Brief Pain Inventory—short form). Quantitative sensory testing was performed according to the protocol of the German Research Network on Neuropathic Pain (DFNS) to assess the somatosensory profiles in the ulnar nerve innervation territory of all participants (dorsum of the hand). Reference data from 50 healthy Indian subjects were within the range of published DFNS values. Somatosensory profiles in leprosy patients with clinically or electroneurographically diagnosed neuropathy (with and without pain) revealed a profile of sensory loss to thermal and tactile stimuli combined with preservation of vibration and deep pressure detection. Sensory gain phenomena were not generally observed in patients with leprosy. In the group of subclinical neuropathy, a high degree of impaired thermal sensation was found, which could be clinically deployed to enhance identification of leprosy neuropathy at an early stage. Quantitative sensory testing can effectively document leprosy-associated neuropathy but does not distinguish between patients with or without pain. Patients with leprosy and neuropathic pain reported a poor quality of life and less psychological well-being compared with the pain-free patients with leprosy neuropathy.